Lauren H. answered • 01/13/19

Experienced High School Chemistry Teacher

**(x-2)(x+3)-(x-4)(2x+5)**

(x - 2)(x + 3) = x^2 + x - 6

(x - 4)(2x + 5) = 2x^2 -3x -20

(x^2 + x - 6) - (2x^2 -3x -20)

x^2 + x - 6 - 2x^2 +3x + 20 = -x^2 + 4x +14

If 0 = -x^2 + 4x +14, then this may be solved with the quadratic equation. However, you did not indicate that it is an equation, only an expression. Therefore it may only be simplified.

Lauren H.

SA = 4Πr^2 Let r = 2, then SA = 4Π2^2 = 4Π4 = 16Π Now, let r = 1, then SA = 4Π1^2 = 4Π So the ratio is 1/4. The surface new area is 1/4 of the original SA.01/13/19

Emelia R.

Can you help me with this problem? The surface area of a sphere is the product of 4 pie and the square of the radius. How does the surface area change when the radius is halved?01/13/19